Analyzing the Corporate Business Intelligence Impact: A Case Study in the Financial Sector - Serap Akcan Yetgin; Hilal Altas (Applied Sciences, 2025)
Business intelligence is the process and methods that enable businesses to effectively analyze large amounts of data and transform it into meaningful information, helping to increase efficiency and productivity in businesses, thus enabling businesses to gain competitive advantage. In this context, business intelligence improves data management and decision-making processes and plays a critical role in strategic management. The main purpose of this study is to analyze the transition process of business intelligence solutions in financial institutions in detail, to increase efficiency in reporting processes, and to optimize decision-making processes. The study examines the ‘Cheque Report’, which reports the status of cheques in XY Financial Institution. Within the scope of the study, the transition process to business intelligence in the financial institution examined the ‘Cheque Report’ in three stages: in the first stage, reports were prepared manually; in the second stage, they were prepared with PL/SQL, and in the last stage, they were prepared with a business intelligence solution, and their outputs were compared. As a result, it was observed that with the use of business intelligence, fast and direct access to reports, data security, freedom from person dependency, and efficiency in internal information sharing are provided.